Sistem Keselamatan Kebakaran Pada Gedung Perpustakaan Universitas Negeri Malang - Tigor, Yosua; Sufianto, Heru (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
The incidence of fires in Indonesia has been increasing year by year. In 2019, there were 92 reported cases of fire in Malang City. The Malang City Fire Department recorded 57 fire incidents from January to mid-July 2023. The number of fire cases in 2023 has increased compared to the previous years, with 66 cases in 2021 and 77 cases in 2022. The predominant cause of these fires is electrical short circuits. The University of Malang Library building, which accommodates various activities within the university area, has a high risk of fire, especially if unsafe practices such as using multi-socket power strips that do not meet standards are present. This can lead to electrical short circuits and potentially cause a fire. Given that this building houses important books and archives and provides electrical facilities to support visitor activities, evaluating the building’s fire safety system is crucial. The purpose of this study is to assess the physical condition of the fire safety system in the University of Malang Library building, focusing on site completeness, rescue facilities, active fire protection systems, and passive fire protection systems. The study also aims to provide recommendations to address existing issues to improve the fire safety performance of the building and prioritize the enhancement of the fire safety system. The findings indicate that although the University of Malang Library has implemented several fire protection systems, there are still areas that need improvement to meet applicable standards, with prioritization based on the issues identified in this study. Keywords: Fire Safety Systems for Buildings, Buildings, Libraries